(untitled) (American Journal of Technology and Applied Sciences, 2026)
This article highlights the importance of social-emotional development in preschool-aged children. It discusses methods for developing skills such as understanding and managing emotions, interacting with others, fostering empathy, and adapting to social norms. The article analyzes how this development impacts a child’s future success.